Silent messages in negotiation: effects of nonverbal behaviors in successful negotiations in Petronas Sdn. Bhd / Noor Fadhilah Md Saad - Md Saad, Noor Fadhilah (Faculty of Business and Management, 2014)
Petroleum Nasional Berhad (PETRONAS) is a growing company which currently leading in oil and gas industry in Malaysia since 1974. As a largest and biggest taxpayer in the country, there are a lot of success and failure story of doing business in this developing country. The purpose of this research is to explore the relationship between the effects of nonverbal behaviors towards the successful negotiation in PETRONAS Sdn. Bhd. Besides that, researcher also going to identify what is the most significant non-verbal behavior that has high impact on the negotiation success in PETRONAS. Based on the findings, the most significant variable that influences successful negotiation in PETRONAS Sdn. Bhd is the kinesics messages. The researcher suggests that company should provide training for the employees to enhance their negotiation skills. As for future researcher, it is suggested to the researcher to study all variable in depth that could explained the strong determined for successful negotiation in details.